Urgensi Media Pembelajaran Dalam Pembelajaran Bahasa Inggris di Sekolah - Mutiara Sofa (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This paper explains the urgency of instructional media in learning English at school. This study aims to analyze the functions and benefits of learning media, the types and uses of learning media, as well as the forms of learning media that can be used in learning English at school. The method in this study uses a qualitative approach with a descriptive method which aims to describe what English learning media can be used in schools. Data collection procedures using content analysis and library research. The use of instructional media includes: 1) Visual Media, 2) Audio Media, 3) Audio Visual Media, 4) Print Media, 5) Model Media, 6) Reality Media, 7) Real objects (Specimen), 8) Computers, 9 ) Multimedia, and 10) Internet. The results of this study explain that it is important to use learning media in learning English at school as an effort to make students easily understand learning material and make classroom situations more lively and not boring, as well as hold direct interactions between students and the environment or real life .